2017
DOI: 10.1590/0101-60830000000120
|View full text |Cite
|
Sign up to set email alerts
|

Current alcohol dependence and emotional facial expression recognition: a cross-sectional study

Abstract: Background: Several studies have demonstrated that chronic and excessive alcohol use causes social cognition deficits. Objectives: Thus, the aim of the current study is to assess the associations between emotional facial expression recognition and current alcohol dependence. Methods: The sample consisted of two groups: one was composed by current alcohol dependent individuals (AG = 110); and a control group, composed of healthy individuals (CG = 110) assessed by the Structured Clinical Interview DSM-IV. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“… Castellano et al (2015) found in the meta-analysis that people with alcohol and substance use disorders had worse facial emotion recognition relative to controls. Donadon and Osório (2017) found that the alcohol-dependent individuals showed low accuracy in recognizing emotions as a whole and especially fear and disgust. In addition, the group needed greater emotional intensity to recognize joy, fear, disgust, and surprise.…”
Section: Discussionmentioning
confidence: 98%
“… Castellano et al (2015) found in the meta-analysis that people with alcohol and substance use disorders had worse facial emotion recognition relative to controls. Donadon and Osório (2017) found that the alcohol-dependent individuals showed low accuracy in recognizing emotions as a whole and especially fear and disgust. In addition, the group needed greater emotional intensity to recognize joy, fear, disgust, and surprise.…”
Section: Discussionmentioning
confidence: 98%
“…This result is consistent with previous studies (Lannoy et al., ) but specifically emphasizes that BD have lower performance for the processing of facial expressions depicting fear and sadness. First, it has been suggested that amygdala lesions may lead to impaired fear processing (Morris et al., ) and this proposal has been supported in SAUDs (e.g., Donadon and Osório, ; O'daly et al., ; Salloum et al., ; Townshend and Duka, ). In binge drinking, amygdala dysfunctions have also been observed (Stephens and Duka, ; Xiao et al., ) and some studies reported impairments in fear processing in preclinical (Stephens et al., ) and human (Herman et al., ) studies.…”
Section: Discussionmentioning
confidence: 98%
“…Fear indeed allows informing about the presence of threat in the environment and is related to the ability to correctly anticipate dangers and implement protective strategies. Accordingly, disrupted fear detection in others might lead to interpersonal problems and might be involved in excessive alcohol consumption (Donadon and Osório, ). Second, this study is the first to underline impairments in the emotional recognition of sadness in binge drinking, and this result is observed in comparison with a control group matched regarding psychopathological variables.…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, 51.1% of the participants were alexithymic, which corroborates the results of international studies. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In this sample, the expression of the EOT subscale has a minor impact on the global score. Alpha Cronbach values´ were consistent for F1 and less consistent for the others factors.…”
Section: Discussionmentioning
confidence: 99%